Value of Caffeic Acid Phenethyl Ester Pretreatment in Experimental Sepsis Model in Rats - Ozlem Alici; Havva Sahin Kavakli; Cemile Koca; Neriman Defne Altintas; Murat Aydin; Suleyman Alici (Hindawi Limited, 2015)
Background and Aim. The aim of this study was to determine the actions of caffeic acid phenethyl ester (CAPE) on the changes of endothelin-1 (ET-1) level, tumor necrosis factor- (TNF-) alpha, and oxidative stress parameters such as superoxide dismutase (SOD) activities and malondialdehyde (MDA) levels in experimental sepsis model in rats. Materials and Methods. Twenty-four rats were randomly divided into three experimental groups: sham (group 1), sepsis (group 2), and sepsis + CAPE (group 3), n = 8 each. CAPE was administered (10 µmol/kg) intraperitoneally to group 3 before sepsis induction. Serum ET-1, serum TNF-alpha, tissue SOD activity, and tissue MDA levels were measured in all groups. Results. Pretreatment with CAPE decreased ET-1, TNF-alpha, and MDA levels in sepsis induced rats. Additionally SOD activities were higher in rats pretreated with CAPE after sepsis induction. Conclusion. Our results demonstrate that CAPE may have a beneficial effect on ET and TNF-alpha levels and oxidative stress parameters induced by sepsis in experimental rat models. Therefore treatment with CAPE can be used to avoid devastating effects of sepsis.